Characterising game styles in the English Premier League using the "moments of play" framework. (2nd November 2018) - Gollan, Stuart; Ferrar, Katia; Norton, Kevin
ABSTRACT: The aim of the current study was to identify different playing styles within 2015–16 English Premier League season. Game-related variables were allocated to the "moments of play" framework, and multidimensional game styles were investigated using cluster analysis and related to finishing position. Totally, 96 game-related variables were allocated into one of five discrete "moments of play"; set pieces (SP), established offence (EO), transition to offence (TO), transition to defence (TD) and established defence (ED). Moments of play variables were z-score transformed. The game-specific mean z-score for the five moments was used as K-means cluster analysis inputs. Relationships between game style clusters and finishing position were investigated using chi-square analysis. Three game style clusters were identified: (1) moderately favouring ED and prevalent among lower-ranked teams ( n  = 270 games); (2) dominant in TO and TD ( n  = 241) and represented by the top team, (3) strong in EO and SP and characterised by higher ranked teams (games n  = 249). Success for the top-ranked team was associated with the dominance in transition moments. Higher ranked teams demonstrate control of EO and SP, whereas lower ranked teams clustered for poor performance in all moments except ED. Game style varies across teams, however, it also aggregates relative to finishing position.